Herman Stachel – a Lviv publisher of popular literature - Gruchała, Irena (Folia Toruniensia, 2018)
Aim: The subject of this article is the Publishing House “Kultura i Sztuka”, a small company run by Herman Stachel in Lviv, which remained on the market thanks to the production of popular books. The main task was the material analysis of the published items, determining their physical characteristics, as well as establishing unknown facts about the activities of Herman Stachel. It was also assumed that the undertaken actions would result in the emergence of writings that about a hundred years ago could count on the interest of the audience. Research method: The study included books appearing in the catalogues of the National Library and the Jagiellonian Library. As a result, a number of unknown facts were given relating to the publishing house and bookstore of Herman Stachel, but this topic has not been exhausted. Results/Conclusions: The analysis of the published texts allowed us to state that the largest group among them constituted literary works written by Polish and foreign authors at the turn of the 19th and 20th centuries. Novels for adults on socio-moral, love and erotic, criminal and historical topics stood out along with satirical works. Literature for children and youth was richly represented. A large group was made up of books popularizing knowledge from various subject areas (psychology, parapsychology, spiritual philosophy, psychiatry, spiritualism, medicine). Guidebooks and cookery books were fewer.